Hubungan Pengetahuan Ibu Tentang Posyandu Dengan Kunjungan Balita Ke Posyandu Di Wilayah Kerja Puskesmas Kedurang Kabupaten Bengkulu Selatan - Denti Yusipa; Dolis Yesti Fennyria; Kristina Paskana (Jurnal Vokasi Kesehatan, 2025)
The behaviour of mothers of toddlers in weighing their children at health posts is influenced by several factors. Knowledge is one of the predisposing factors that influence a person's behaviour. Mothers with good knowledge have an understanding of health post activities such as the purpose of weighing, the purpose of PMT and the importance of immunisation, so that the higher the level of knowledge of mothers, the higher the frequency of visits to health posts. Objective: To determine the relationship between mothers' knowledge about posyandu and infant visits to posyandu in the working area of the Kedurang Health Centre, South Bengkulu District. This study employed an analytical method with a cross-sectional approach. The study population consisted of all infants with a KIA book in the working area of the Kedurang Health Centre, South Bengkulu District, in May 2024, with a sample of 89 mothers with infants. Data analysis was performed using the chi-square test. The results showed that most mothers had good knowledge (56.2%), but infant visits to the posyandu were insufficient (55.1%). The chi-square test revealed a p-value of ρ(0.00) < ρ(0.05). There is a significant relationship between mothers' knowledge about posyandu and infant visits to the posyandu in the service area of the Kedurang Health Centre, South Bengkulu District.